Cross neutralization of afro-asian cobra and asian krait venoms by a thai polyvalent snake antivenom (neuro polyvalent snake antivenom) - Leong, P.K.; Sim, S.M.; Fung, S.Y.; Sumana, K.; Sitprija, V.; Tan, N.H. (2012)
BACKGROUND: Snake envenomation is a serious public health threat in the rural areas of Asian and African countries. To date, the only proven treatment for snake envenomation is antivenom therapy. Cross-neutralization of heterologous venoms by antivenom raised against venoms of closely related species has been reported. The present study examined the cross neutralizing potential of a newly developed polyvalent antivenom, termed Neuro Polyvalent Snake Antivenom (NPAV). NPAV was produced by immunization against 4 Thai elapid venoms. PRINCIPAL FINDINGS: In vitro neutralization study using mice showed that NPAV was able to neutralize effectively the lethality of venoms of most common Asiatic cobras (Naja spp.), Ophiophagus hannah and kraits (Bungarus spp.) from Southeast Asia, but only moderately to weakly effective against venoms of Naja from India subcontinent and Africa. Studies with several venoms showed that the in vivo neutralization potency of the NPAV was comparable to the in vitro neutralization potency. NPAV could also fully protect against N. sputatrix venom-induced cardio-respiratory depressant and neuromuscular blocking effects in anesthetized rats, demonstrating that the NPAV could neutralize most of the major lethal toxins in the Naja venom. CONCLUSIONS/SIGNIFICANCE: The newly developed polyvalent antivenom NPAV may find potential application in the treatment of elapid bites in Southeast Asia, especially Malaysia, a neighboring nation of Thailand. Nevertheless, the applicability of NPAV in the treatment of cobra and krait envenomations in Southeast Asian victims needs to be confirmed by clinical trials. The cross-neutralization results may contribute to the design of broad-spectrum polyvalent antivenom.